2017
DOI: 10.1177/2047487317722913
|View full text |Cite
|
Sign up to set email alerts
|

Validation and recalibration of the Framingham cardiovascular disease risk models in an Australian Indigenous cohort

Abstract: BackgroundIn Australia, clinical guidelines for primary prevention of cardiovascular disease recommend the use of the Framingham model to help identify those at high risk of developing the disease. However, this model has not been validated for the Indigenous population.DesignCohort study.MethodsFramingham models were applied to the Well Person’s Health Check (WPHC) cohort (followed 1998–2014), which included 1448 Aboriginal and Torres Strait Islanders from remote Indigenous communities in Far North Queensland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 26 publications
2
50
1
1
Order By: Relevance
“…While studies in remote communities have shown that, applied alone, FRE underestimates the risk of CVD events, these findings may not apply to all Aboriginal and Torres Strait Islander peoples. The findings from these communities are likely to reflect a clustering of non‐FRE risk factors, including socio‐economic disadvantage, rather than an inherent underestimation of CVD risk due to race.…”
Section: Optimising the Approach To Aboriginal And Torres Strait Islamentioning
confidence: 85%
See 1 more Smart Citation
“…While studies in remote communities have shown that, applied alone, FRE underestimates the risk of CVD events, these findings may not apply to all Aboriginal and Torres Strait Islander peoples. The findings from these communities are likely to reflect a clustering of non‐FRE risk factors, including socio‐economic disadvantage, rather than an inherent underestimation of CVD risk due to race.…”
Section: Optimising the Approach To Aboriginal And Torres Strait Islamentioning
confidence: 85%
“…Until these risk calculators are updated, when assessing absolute CVD risk in Aboriginal and Torres Strait Islander peoples aged 30–34 years, clinicians should enter an age of 35 years. Studies comparing predicted and observed numbers of CVD events in remote Aboriginal and Torres Strait Islander populations have shown that FRE underestimates the risk of CVD events in people aged less than 35 years . Therefore, the use of a slightly older age in these situations is unlikely to significantly inflate CVD risk.…”
Section: Optimising the Approach To Aboriginal And Torres Strait Islamentioning
confidence: 99%
“…‐ 27 However, data on the exact probability of CVD events in people with each condition by age are limited, especially at younger ages and for Aboriginal and Torres Strait Islander people. Further validation and calibration of CVD risk assessment for Aboriginal and Torres Strait Islander people is needed to improve CVD prevention 28 …”
Section: Discussionmentioning
confidence: 99%
“…Further validation and calibration of CVD risk assessment for Aboriginal and Torres Strait Islander people is needed to improve CVD prevention. 28 Although estimates from the AATSIHS sample are considered to be nationally representative, the survey did not sample individuals from non-private dwellings (eg, hotels, short stay caravan parks, hospitals, prisons). However, our sample was the largest and most representative sample of an indigenous population, in Australia or elsewhere, ever assessed for CVD risk, and population weights were applied to achieve reliable estimates.…”
Section: Ethics Approvalmentioning
confidence: 99%
“…While the annual CVD risk assessment using a validated absolute risk algorithm has been recommended for Indigenous Australians [7], there is widespread belief that current tools have deficiencies in assessing CVD risk in this high risk population [6,8,9]. Several studies have shown that the equations derived from the Framingham study underestimate the CVD risk of Indigenous Australians [10,11]. One explanation for this underestimation may be that certain CVD risk factors for Indigenous people such as albuminuria and waist circumference are not included in the Framingham CVD equations [2,3,12,13].…”
Section: Introductionmentioning
confidence: 99%